A Narrative Inquiry of Students’ Experiences on Public Speaking Club Activities - Pravitasari, Hikmah; Bagus Paripurna , Muhammad (Journal of Literature Language and Academic Studies, 2024)
This study explores students’ experiences in public speaking club activities related to their challenges and strategies. This study used a narrative inquiry as the research method. The research data were obtained from in-depth interviews and students’ weekly journals. The participants in this study were two students who are the most active students in the public speaking club at a private Islamic senior high school in Indonesia. The research data were analyzed using thematic analysis. The results of this study showed that the students’ experiences regarding the challenges faced in public speaking were linguistics and non-linguistics problems. The linguistics problems faced by students were pronunciation, grammar, and vocabulary. Besides, non-linguistic problems faced by students consisted of anxiety and lack of self-confidence. The strategies used by the students to overcome the challenges in public speaking were understanding materials, memorizing some new vocabulary, practicing with friends and requesting their feedback, and practicing alone in front of a mirror. This study is limited in location, the number of participants and the type of research instrument. It is recommended for further research to be able to conduct similar research by changing the level of participants and adding variations of research instruments.